A framework of transparency initiative (TI) to fight corruption for public construction projects / Rumaizah Mohd Nordin - Mohd Nordin, Rumaizah (2015)
Transparency is defined as the open flow of information and an essential element of the Government primary approach to reduce corruption. The prime reason for dealing with corruption problem is to promote transparency for all businesses. In Malaysia, fighting corruption is one of the National Key Results Area (NKRA) under the Government Transformation Program (GTP). Corruption is a fiduciary crime that is believed to penetrate the construction sectors in countries around the world. Given the intrinsically secretive nature of corrupt activities, the construction industry has a worldwide reputation for incidences of corruption and as for Malaysia; the issue of corruption in construction is at a serious level. Despite corruption exists in every stage of project life cycle, most of the issue of corruption focused at the procurement phase. Besides, sources of corruption can be divided into technical and behavioural issues. Undoubtedly corrupt practices have a lot of adverse effects on the industry as corruption may cause inefficiency and ineffectiveness on project performance. In recent years, anti-corruption strategy has been high on agenda in many parts of the world but relatively little examines the problem in a sector specific way. Regardless of many strategies in combating corruption has been undertaken in Malaysia, there is a need to revise for a more drastic anti-corruption strategies to implement it effectively. The failure in coping with corruption partly stems from our lacking adequate analytical framework that would allow us to sufficiently understand its nature and causal linkage to economic development. Moreover, at present there is no framework of TI formulated to provide a systematic reading on the issues of corruption and means to reduce it especially in construction sector in Malaysia. Thus, the aim of this research is to develop a framework of transparency initiative (TI) to fight corruption for public construction projects. The empirical research was undertaken in two phases; Preliminary Study (i.e., exploratory interviews - 8 respondents, a brain-storming workshop - 72 participants, and document analysis - 4 documents) and Main Survey (i.e., questionnaire - 71 responses) with respondents from Government agencies, contractors and consultants. The data from the Preliminary Study was analysed utilising thematic content analysis and qualitative software (Atlas t.i version 7) whilst the questionnaire survey was analysed using the Statistical Package for the Social Sciences (SPSS) software version 21. The findings from the research were used to develop a framework to fight corruption through TI which was validated to confirm its external validity. The findings confirmed that the level of corruption is high in Malaysian construction industry and procurement phase is the most vulnerable area for corrupt practices. Besides, transparency was found to be important in reducing corruption in term of creating norms for ethical behaviour or in improvement of process of work. However, the research reveals that behavioural issue is one of the important sources of corruption that is negatively related to transparency improvement in order to fight corruption. The framework of TI to fight corruption may serve as a guideline for project stakeholders in achieving better performance of construction project with reduced corruption.